Attendance System Design Based Mobile Employees to Detect Location Global Positioning System (Gps) And International Mobile Equipment Identity (Imei) Smartphone at Pt. Inovasi Dinamika Solusi - Rofiyani, Indah; Sy, Rivalda Alvandiaz; Irwansyah P, Rian Erlangga; Tobing, Indra Gunawan; Chaniago, Muhammad Benny (International Journal of Psychosocial Rehabilitation, 2020)
• Inovasi Dinamika Solusi is an information technology consultant who recently founded in 2017. The company has several employees that the data must be well-organized, especially in terms of employee attendance are currently no special recording of attendance itself is simply done by using a recording Microsoft Excel gained from history logs report the work, if the employee does not fill the log is then considered to be absent. This way the data can not be used as a reference for reporting and undermining some of the parties because in the process of recording attendance is not recorded in realtime. Information obtained become incompatible and can not be accounted for. The method used Prototype. The prototype method begins by listening to the needs and feedback from users. The design of this android based attendance system provides a feature absent present and return to check the GPS location, check the IMEI is registered on the account with the IMEI on the device. GPS is used to determine the location (tracking) the location of employee conduct must be absent due to the office area, smartphone IMEI is used to determine that the employees use the same smartphone to do absent. With the attendance of an information system based on Android is expected to become operational tools PT. Inovasi Dinamika Solusi.